1966
DOI: 10.1111/j.1365-2621.1966.tb03283.x
|View full text |Cite
|
Sign up to set email alerts
|

Composition of Raw and Roasted Lamb and Mutton II. Amino Acids

Abstract: Microbiological assay values are reported for content of 18 amino acids in separable lean of raw and roasted rib-loin and leg cuts of lamb and mutton.These values agreed well with values obtained in other laboratories.The amino acid content of lamb protein tended to be constant and was not affected by cut or by roasting.Retentions of amino acids in lamb lean after roasting were essentially complete.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1969
1969
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In casein heated at 130 °C for 8 h, only a 4% decrease in the availability of tryptophan was observed as measured by the growth of Streptococcus zymogenes (Osnet and Johnson, 1975). No reduction in the availability of this amino acid as measured by Leuconostoc mesenteroid.es was observed when lamb or mutton meat was cooked in an oven (Blum et al, 1966). However, heating cod muscle at 85 °C for 27 h reduced the availability by 16.5% as measured by S. zymogenes growth (Miller et al, 1965).…”
Section: Nutritionmentioning
confidence: 99%
“…In casein heated at 130 °C for 8 h, only a 4% decrease in the availability of tryptophan was observed as measured by the growth of Streptococcus zymogenes (Osnet and Johnson, 1975). No reduction in the availability of this amino acid as measured by Leuconostoc mesenteroid.es was observed when lamb or mutton meat was cooked in an oven (Blum et al, 1966). However, heating cod muscle at 85 °C for 27 h reduced the availability by 16.5% as measured by S. zymogenes growth (Miller et al, 1965).…”
Section: Nutritionmentioning
confidence: 99%
“…Lamb meat, containing high content of protein, essential amino acids and essential fatty acids, has become increasingly popular around the world in recent years (Blum et al ., 1966; Bekhit et al ., 2021a). However, the high water content and the abundance of nutrients on lamb meats' surface make it become one of the most perishable types of food, which could cause a huge waste of meat resources and endanger human health directly (Zhang et al ., 2012; Carrizosa et al ., 2017; Yin et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Colombo et al, 1958), cooking (Ginger THE TOTAL amino acid composition of et al, 1954;Zoltowska, 1967), and muscle protein is quite constant regard-frozen storage time and temperature less of the species or the muscle from (Golovkin et al, 1966). Ma et al (1961) which it is obtained (Lyman et al, 1949;and Usborne (1967) have shown that Schweigert et al, 1945;Blum et al, greater amounts of certain free amino 1966). Nevertheless, free amino acid acids are related to more tender beef and composition of muscle has been reported pork, respectively.…”
mentioning
confidence: 95%